Perlindungan Hukum Terhadap Penetapan Status Tersangka Ditinjau Dari Perspektif Hak Asasi Manusia - Amin, Khoirul (Universitas Sunan Drajat Lamongan, Indonesia, 2024)
Legal protection for suspects is a guarantee of legal protection provided by law for the recognition of the rights of a suspect. Despite the status of a suspect, a person still has a number of rights that must be fulfilled and respected. If these rights are violated, then it means that the human rights of the suspect have been violated or not respected. Law Number 8 of 1981 concerning the Code of Criminal Procedure (KUHAP) has regulated the rights of suspects from Article 50 to Article 68 of the Code of Criminal Procedure. The problem is, if there is a person who has been determined as a suspect by investigators, while the status of the suspect is suspended for years without any further legal process to be tried in court. Even though suspects have the right to immediately get legal certainty and justice. The method used in this study is normative legal research conducted as an effort to obtain the necessary data in connection with the problem. Data used with skunder data and tertiary law materials. In addition, primary data is also used as a support for secondary data legal materials. From the results of the study showed that there is a legal vacuum to the regulations governing the time limit for determining a person to be a suspect. Article 50 of the Criminal Procedure Code only regulates the provision of time for handling cases, or commonly known as the right to priority settlement of case. So that the rights inherent in the suspect must be respected by all parties, especially by law enforcement officers. By suspending the status of a person's suspect and allowing it to drag on, the suspect's right to immediately obtain justice and legal certainty on matters that are suspected of him has clearly been violated.